A teledentistry care model for older populations in remote settings in Chile using satellite communication technology - Beltrán, Víctor; López, Leonardo; Acuña-Mardones, Pablo; Silva, Roberto; Acevedo, Claudia; Bustos, Jaime; Alarcón, Claudio; von Marttens, Randal; Espinoza, Iris; Mariño, Rodrigo (Frontiers in Oral Health, 2025)
ObjectivesThe aim of this study is to provide initial evidence of the impact of teledentistry, using satellite communication technology to improve access to oral healthcare in underserved populations in rural and remote areas.MethodsA pilot model of teledentistry care for older adults, incorporating technological and clinical components with a satellite solution for areas without connectivity, was evaluated in the Los Lagos Region, Chile. This was classified in terms of the sequential industrial modernization framework and technology types.ResultsThirty-one older adults participated in this evaluation, with a mean age of 66.3 years. The majority (56%) had not visited a dentist in over five years. The average DMFT index was 24.2 teeth, with almost half of the participants (45.4%) presenting unmet restorative needs, and 83.3% required prosthetic appliances. A large proportion of the sample requiring a referral for emergency treatment. Most consultations (84%) were for emergency care, predominantly due to dental pain. The strategy was classified as part of the Industry 4.0 trend of modernization, with elements of the Industry 3.0.ConclusionThis piloted model of care can enhance care access and improve health outcomes for isolated populations. This innovative model of care ensured that all participants received oral health assessments, addressing the need for the systematic identification of older adults at risk of oral health emergencies. Future directions could include the integration of contextual artificial intelligence and expansion into other underserved areas, reinforcing the role of digital ecosystems in enhancing access to care and reducing health disparities.